TANTANGAN DAN PROSPEK SARJANA AGRIBISNIS DALAM PERSPEKTIF ALUMNI EMPAT PERGURUAN TINGGI NEGERI DI JAWA TIMUR - Syahputra, Syaifullah; Nugroho, Sigit Dwi; Hidayat, Syarif Imam (Berkala Ilmiah AGRIDEVINA, 2021)
The agricultural sector is not only influenced by the technology, but also influenced by human resources. Human resources in the agricultural sector has a very important to improve the agricultural sector in Indonesia. The agricultural sector in Indonesia is currently experiencing a phenomenon of the aging farmers that is not in balance with the regeneration of young farmers, So also many scholars agribusiness who work outside the agricultural sector. It is a serious problem for the agricultural sector in Indonesia. The purpose of this Study is to Analyze the Challenges and Prospects of Bachelor of Agribusiness in the future based on the Perceptions of Alumni of the department Agribusiness Four National University in East Java. Determination of the respondents using a Quota sampling technique by using Respondents from the Alumni of the department of Agribusiness Four National University in East Java. Four alumni of the university that made the respondents are Brawijaya University, Jember University, Trunojoyo University and National Development “Veteran” East Java University. Following analyzed data collected using analysis descriptive and presented in the form of a Table. The results of the Analysis showed that the Main Challenges Undergraduate Agribusiness is the Revolution of Industry 4.0 with the actual  score 4,45 as well as the percentage of 89% and the Prospect of Bachelor of Agribusiness has an average score of 3,68 with the percentage of 73,62% to get into the good category. DOI : https://doi.org/10.33005/adv.v10i1.2556